2022
DOI: 10.1080/22221751.2022.2078226
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus serotype 9 AAV-RABVG expressing a Rabies Virus G protein confers long-lasting immune responses in mice and non-human primates

Abstract: Three or four intramuscular doses of the inactivated human rabies virus vaccines are needed for pre- or post-exposure prophylaxis in humans. This procedure has made a great contribution to prevent human rabies deaths, which bring huge economic burdens in developing countries. Herein, a recombinant adeno-associated virus serotype 9, AAV9-RABVG, harbouring a RABV G gene, was generated to serve as a single dose rabies vaccine candidate. The RABV G protein was stably expressed in the 293T cells infected with AAV9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In our study, significantly more mature cDCs were detected in inguinal lymph nodes in Adv-RVDG than Adv-RVG vaccinated mice, which may be attributed to the increased level of RVG expression. Similar results were observed in AAV9-RABVG vaccinated mice [ 56 ]. Logically, more robust germinal centre responses were produced the inguinal lymph nodes of Adv-RVDG immunized mice including Tfh cells differentiation, GC B cells proliferation, and more antibody-secreting cells production.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, significantly more mature cDCs were detected in inguinal lymph nodes in Adv-RVDG than Adv-RVG vaccinated mice, which may be attributed to the increased level of RVG expression. Similar results were observed in AAV9-RABVG vaccinated mice [ 56 ]. Logically, more robust germinal centre responses were produced the inguinal lymph nodes of Adv-RVDG immunized mice including Tfh cells differentiation, GC B cells proliferation, and more antibody-secreting cells production.…”
Section: Discussionsupporting
confidence: 88%
“…Current commercial inactivated vaccines have relatively poor immunogenicity and require repeated injections. In recent years, numerous studies have been carried out to develop novel, safe, and effective rabies vaccines, such as recombinant virus-vector vaccines (33)(34)(35)(36)(37)(38), DNA and RNA-based vaccines (15,16,27,28), live attenuated rabies vaccines (39), and protein vaccines (40). In this study, we mainly demonstrated that a single immunization of nucleoside-modified RABV-G mRNA vaccine induced a more potent immunogenic response than commercial inactivated rabies vaccines, providing complete protection against lethal rabies virus challenge, and induced durable NAb responses in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%